2018
DOI: 10.1016/j.accinf.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of client information technology capability on audit pricing

Abstract: This paper explores the question: "How does a client's information technology (IT) capability influence audit pricing?" Company data for the years 2004 through 2012 are employed. Firms appearing on the InformationWeek 500 (IW500) annual list of U.S. organizations with superior IT functions serve as a proxy for companies with superior IT capability. Our findings suggest that companies with superior IT capabilities incur higher levels of audit fees. In addition, as client size increases, the audit fees of firms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…In this study, no direct effect of ITCAP was found on creativity, excellence, risk tolerance or proactive orientation. This confirms the results of Hoffman et al (2018), suggesting that ITCAP do not always make competitive advantage. We can conclude that the existence of ITCAP in itself does not promote a proactive approach to seize opportunities and entrepreneurial creativity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, no direct effect of ITCAP was found on creativity, excellence, risk tolerance or proactive orientation. This confirms the results of Hoffman et al (2018), suggesting that ITCAP do not always make competitive advantage. We can conclude that the existence of ITCAP in itself does not promote a proactive approach to seize opportunities and entrepreneurial creativity.…”
Section: Discussionsupporting
confidence: 87%
“…Following these seminal works, researchers have reported that MM remains a prominent factor that potentially influences entrepreneurship in a variety of studies (Bilal and Al Mqbali, 2015; Colbert, 2003; Miles and Darroch, 2006; Morris and Lewis, 1995; Arora and Nandkumar, 2012; Carson et al , 1995; Collinson and Shaw, 2001; Bocconcelli et al , 2018; Hultman and Hills, 2011; Knight, 2000; Solé, 2013; Barrett et al , 2000; Nasution et al , 2011; Kraus et al , 2010; Stokes, 2000). Relatedly, studies have also indicated the importance of information technology capabilities (ITCAP) for influencing entrepreneurship effectively (Chen et al , 2014; Chen et al , 2015; Trainor et al , 2011; Chae et al , 2018; Hoffman et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For a robustness check, we use alternative measures of audit efficiency: audit hours and audit fees. Previous research (Hoffman et al, 2018;Knechel et al, 2009) found that audit hours and fees are closely related to audit efficiency.…”
Section: Alternative Measures: Audit Hours and Feesmentioning
confidence: 98%
“…Moreover, as suggested by practitioners (Deloitte, 2015; Hoffman et al, 2018; PwC et al, 2015), audit performance depends on the level of sophistication of the IT system, which is generally determined by the quality of personnel who establish the system (Janvrin et al, 2008; Vasarhelyi et al, 2012). IC personnel with more work experience in the IT department could provide appropriate audit evidence using the established IT system based on their knowledge about how business transactions are recorded and configured, thereby contributing to enhanced audit efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…(Yamamoto, 2017), (Hosono & Shimomura, 2017), (Al-Matari, Helal, Mazen, & Elhennawy, 2021), (Ariffin & Ahmad, 2021), (Alimam, Bertin, & Crespi, 2017), (Shrestha, Cater-Steel, Toleman, Behari, & Rajaeian, 2020), (Proença & Borbinha, 2016), (Schmitz, Schmid, Harborth, & Pape, 2021), (Yandri, Suharjito, Utama, & Zahra, 2019), (Orta & Ruiz, 2019) Knowledge Worker Factor Knowledge workers factor are those who are able to provide assessments using systemic thinking and who can apply systematic approaches, best practices, and tools to utilize IT effectively. (Gantman & Fedorowicz, 2016), (Ariffin & Ahmad, 2021), (Alreemy, Chang, Walters, & Wills, 2016), (Yandri, Suharjito, Utama, & Zahra, 2019), (Terlizzi, Albertin, & de Moraes, 2017), (Hoffman, Sellers, & Skomra, 2018), (Bounagui, Mezrioui, & Hafiddi, 2019), (Amorim, Mira da Silva, Pereira, & Gonçalves, 2021)…”
Section: Design Factormentioning
confidence: 99%